Photosensitization With Supramolecular Arrays for Enhanced Antimicrobial Photodynamic Treatments - Vera, Cecilia; Tulli, Fiorella; Borsarelli, Claudio D. (Frontiers in Bioengineering and Biotechnology, 2021)
Microbial infections represent a silent threat to health that has worsened in recent decades due to microbial resistance to multiple drugs, preventing the fight against infectious diseases. Therefore, the current post-antibiotic era forces the search for new microbial control strategies. In this regard, antimicrobial photodynamic therapy (aPDT) using supramolecular arrays with photosensitizing capabilities showed successful emerging applications. This exciting field makes it possible to combine applied aspects of molecular photochemistry and supramolecular chemistry, together with the development of nano and biomaterials for the design of multifunctional or “smart” supramolecular photosensitizers (SPS). This mini-review aims to collect the concepts of the photosensitization process and supramolecular chemistry applied to the development of efficient applications of aPDT, with a brief discussion of the most recent literature in the field.